Identifikasi Pekarangan Rumah Percontohan Program "HATINYA" di Kecamatan Denpasar Utara, Kota Denpasar - Vedatya, Putu Devamirna; Sugianthara, Anak Agung Gede; Pradnyawathi, Ni Luh Made (Jurnal Arsitektur Lansekap; Vol. 10, No. 2 Oktober 2024, 2024)
The PKK "HATINYA" program is the use of existing land and yards to plant useful plants, according to regional potential, at least to meet family needs. There is a house that will be used as a pilothouse in this program. This research was conducted to identify the yard of the pilothouse in the PKK "HATINYA" program in the North Denpasar District, especially in Ubung Kaja Village so that it is expected to be a reference for the development of other home yards. The research method used is a survey method with qualitative descriptive analysis methods and data collection techniques of observation, interviews, and literature study. The results showed the pattern of the yard space using the Tri Mandala Balinese Cultural Philosophy Concept. The placement of the plants is adjusted based on the space pattern and is divided based on the function of the plant, including the function of ceremonies, TOGA, fruits, vegetables, herbs, and ornamental plants. Planting in the merajan area or the Utama Mandala uses the Dewata Nawa Sanga concept. The yard model can be applied to a narrow (60 m 2 ), medium (200 m 2 ), and wide (500 m 2 ) yard, however it requires various adjustments such as plant type, number, planting pattern, and planting location. It is necessary to do further research on the yard that uses the traditional Balinese yard concept with the concept of laying traditional Balinese buildings so that in the future it can be used as a reference for the yard model.